Assessment of endocrine disruption and oxidative potential of bisphenol-A, triclosan, nonylphenol, diethylhexyl phthalate, galaxolide, and carbamazepine, common contaminants of municipal biosolids. (April 2018) - Cavanagh, Jo-Anne E.; Trought, Katherine; Mitchell, Caroline; Northcott, Grant; Tremblay, Louis A.
Abstract: The use of biosolids as a soil conditioner and fertiliser is hindered by the limited knowledge on the risks of micro-contaminants they contain. This study investigated the binding of six organic contaminants commonly found in biosolids, to the estrogen (ER), androgen (AR), aryl hydrocarbon (AhR), and transthyretin (TTR) receptors and their redox activity. Triclosan (TCS), bisphenol-A (BPA), and technical nonylphenol (TNP) had affinity for the TTR with relative potencies of 0.3, 0.03, and 0.076 respectively. Further, binding to TTR was the only toxicological response observed for carbamazepine, which induced sub-maximal response and relative potency of 0.0017. Estrogenic activity was induced by BPA, galaxolide (HHCB), diethylhexyl phthalate (DEHP) and TNP with BPA having the strongest potency of 5.1 × 10 −6 relative to estradiol. Only BPA showed androgenic activity but it was not quantifiable. BPA also showed anti-androgenic activity along with TCS, HHCB, and TNP in the order of TNP > HHCB > TCS BPA (relative potencies 0.126, 0.042, 0.032, 0.03). No compounds exhibited anti-estrogenic or AhR activity, or were redox-active in the dithiothreitol assay. The results highlight the multiple modes of action through which these compounds may impact exposed organisms, and the concentrations at which effects may occur. This allows assessment of the likelihood of effects being observed at environmental concentrations, and the potential contribution of these compounds. Highlights: Relative potency determined for six individual contaminants in a suite of bioassays Multiple-modes of action of individual contaminants demonstrated in different in vitro assays Comprehensive assessment of potential in vitro effects associated with carbamazepine